Psychological Sequelae Resulting From the 2004 Florida Hurricanes: Implications for Postdisaster Intervention - Acierno, Ron (American Public Health Association, 2007)
Objectives. Data are limited regarding mental health effects of disasters such as hurricanes. We sought to determine the prevalence of and major risk factors associated with posttraumatic stress disorder (PTSD), generalized anxiety disorder, and major depressive episode 6 to 9 months after the 2004 Florida hurricanes. Methods. Random-digit dialing was used to recruit a representative population sample of 1452 hurricane-affected adults. Results. Posthurricane prevalence for PTSD was 3.6%, for generalized anxiety disorder was 5.5%, and for major depressive episode was 6.1%. Risk factors varied somewhat across disorders, with the exception of previous exposure to traumatic events, which increased risk of all negative outcomes. Conclusions. Storm exposure variables and displacement were associated primarily with PTSD. Notably, high social support in the 6 months preceding the hurricanes protected against all types of disorders.